Thermostable and Long-Circulating Albumin-Conjugated Arthrobacter globiformis Urate Oxidase - Byungseop Yang; Inchan Kwon (MDPI AG, 2021)
Urate oxidase derived from Aspergillus flavus has been investigated as a treatment for tumor lysis syndrome, hyperuricemia, and gout. However, its long-term use is limited owing to potential immunogenicity, low thermostability, and short circulation time in vivo. Recently, urate oxidase isolated from Arthrobacter globiformis (AgUox) has been reported to be thermostable and less immunogenic than the Aspergillus-derived urate oxidase. Conjugation of human serum albumin (HSA) to therapeutic proteins has become a promising strategy to prolong circulation time in vivo. To develop a thermostable and long-circulating urate oxidase, we investigated the site-specific conjugation of HSA to AgUox based on site-specific incorporation of a clickable non-natural amino acid (frTet) and an inverse electron demand Diels-Alder reaction. We selected 14 sites for frTet incorporation using the ROSETTA design, a computational stability prediction program, among which AgUox containing frTet at position 196 (Ag12) exhibited enzymatic activity and thermostability comparable to those of wild-type AgUox. Furthermore, Ag12 exhibited a high HSA conjugation yield without compromising the enzymatic activity, generating well-defined HSA-conjugated AgUox (Ag12-HSA). In mice, the serum half-life of Ag12-HSA was approximately 29 h, which was roughly 17-fold longer than that of wild-type AgUox. Altogether, this novel formulated AgUox may hold enhanced therapeutic efficacy for several diseases.